Building Public Values Through Strengthening Consumer Dispute Resolution : A Study of the Implementation of the Bandung City Bpsk Socialiization in Gedebage District - Salamatul Afiyah (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract This study originates from the persistent issue of information asymmetry and low legal literacy among consumers in Gedebage District, Bandung City, despite the formal availability of the Consumer Dispute Settlement Board (BPSK) as a non-litigation mechanism. Against this backdrop, the research aims to examine how BPSK’s outreach activities are implemented and, interestingly, how these efforts contribute to strengthening consumer protection, generating public value, and enhancing legal awareness among community members. The theoretical framework draws on the concepts of public value, consumer protection, and legal awareness, which position outreach initiatives as essential governance instruments for expanding access to justice. Employing a descriptive qualitative approach through in-depth interviews, field observations, and document analysis the study finds that BPSK’s face-to-face and dialogic outreach, supported by symbols of legal authority, effectively improves public understanding of consumer rights and dispute procedures while reducing information gaps between consumers and businesses. These findings suggest that contextual and sustained outreach designs have strong potential to be replicated as consumer protection strategies in other regions and provide an empirical foundation for strengthening future BPSK outreach policies. Keywords: BPSK, Consumer Protection, Public value.